2008
DOI: 10.1128/aem.00387-08
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of the Bacterial Communities in the Different Compartments of a Full-Scale Reverse-Osmosis Water Purification Plant

Abstract: The origin, structure, and composition of biofilms in various compartments of an industrial full-scale reverse-osmosis (RO) membrane water purification plant were analyzed by molecular biological methods. Samples were taken when the RO installation suffered from a substantial pressure drop and decreased production. The bacterial community of the RO membrane biofilm was clearly different from the bacterial community present at other locations in the RO plant, indicating the development of a specialized bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
86
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(97 citation statements)
references
References 46 publications
9
86
0
2
Order By: Relevance
“…In terms of microbial species, the work of Bereschenko et al found that members of the genus Sphingomonas played a very important role in the initial formation and subsequent maturation of biofilms on RO membrane [27,28]. Because they are facultative oligotrophs, they are metabolically well adapted to a low-carbon environment and can proliferate under conditions of limited substrates.…”
Section: Bacterial Adhesion: General Patternsmentioning
confidence: 99%
“…In terms of microbial species, the work of Bereschenko et al found that members of the genus Sphingomonas played a very important role in the initial formation and subsequent maturation of biofilms on RO membrane [27,28]. Because they are facultative oligotrophs, they are metabolically well adapted to a low-carbon environment and can proliferate under conditions of limited substrates.…”
Section: Bacterial Adhesion: General Patternsmentioning
confidence: 99%
“…Once in process, biofouling continually and intensively hinders the RO filtration process. Additionally, the construction of "spiral-wound" membrane units, spacers between the membranes, additional inner surfaces, roughness of the membrane surface, and processing conditions also make these membranes susceptible to microbial attachment, leading to the formation of biofilm layers (Bereschenko et al, 2008(Bereschenko et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…An inorganic precipitation or scaling layer in contrast would reveal a sandpaper-like structure on the membrane surface. Furthermore, at location III, biofouling was reported in earlier studies and several biofouling key studies were performed at this location [20][21][22][23]. To differentiate between organic fouling and biological fouling, TOC, polysaccharides, proteins, and CFU measurements ( Figure 5) and SEM were performed.…”
Section: Membrane Fouling Characterization By Membrane Autopsies Of Fmentioning
confidence: 97%
“…At locations II and III, the low pH cleaning is performed with a commercial mixed acid detergent, intended to improve foulant solubility. At location III, which has been extensively studied for its biofouling problems [20][21][22][23], sodium bisulfite is used during the high pH cleaning in order to achieve anoxic conditions and improved microbial inactivation. The volumetric flow rate during cleaning at all locations is 9 m 3 h −1 for each membrane vessel in the first stage.…”
Section: Membrane Cleaning and Performance In Fullmentioning
confidence: 99%
See 1 more Smart Citation